Adsorptive removal of Cr (VI) from wastewater using magnetite–diatomite nanocomposite - Lemessa, Gemechu; Chebude, Yonas; Alemayehu, Esayas (Aqua (London, England), 2023)
Magnetite-diatomite nanocomposite was synthesized through co-precipitation methods as an effective Cr(VI) removal adsorbent. The properties of diatomite, thermochemically modified diatomite (TMD), and magnetic–diatomite nanocomposite (MDN) were investigated using Fourier-transform infrared spectroscopy, X-ray diffraction analysis, Brunauer–Emmett–Teller, and complete silicate chemical analysis. The MDN shows 98.89% adsorption removal at optimized conditions using the response surface methodology of Box–Behnken Design. The kinetic data for Cr(VI) sorption on MDN were well described by pseudo-second order, which indicates the Cr(VI) adsorption was mainly due to chemisorption. The isotherm data show that the Langmuir and Freundlich models better described Cr(VI) ion sorption data. The thermodynamic parameters ΔG°, ΔH°, and ΔS° were estimated, and the results indicate Cr(VI) sorption on MDN was a spontaneous (ΔG° < 0) and exothermic process (ΔH° < 0). The proper Fe3O4 loading into TMD improves the gram susceptibility (Xg) of MDN for magnet separation. The regeneration of nanocomposite material revealed over 80% Cr(VI) removal efficiency after five consecutive adsorption–desorption cycles. The produced MDN was tested for the removal of Cr(VI) from real tannery wastewater. The obtained results suggest the possibility of using this nanocomposite as an effective, efficient adsorbent to remove Cr(VI) laden wastewater.